VISUALIZATION TOOLS IN HUMANS DIGESTION USING MACROMEDIA FLASH 5.0 - Rendy Bayutriilaksono; Irfan Irfan, Skom, MM (Jurnal Sistem Informasi, 2002)
With the increasing development of technology, at this time the computer is not onlyused as a tool for typing, counting only. Now the computer is used to create images,combine images, and moving images. Where the moving picture that has beenmerged with the animation is called.Animation, before the computer was developed, has been known in film making. Asan example of this is a cartoon, but at the present animated t dapa also used as ameans of teaching. Given this, the specific areas on a lesson (Biology), which can notbe described directly, it can be seen through this application.So the teacher as a teacher can explain a material and students can more clearlyaccept or understand the materials given. So the problems that arise in the field ofbiology teaching in particular subjects can be completed.With this application, so students can learn to understand the materials given,especially in the digestive process as you play.